1999
DOI: 10.1001/jama.281.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic–Resistant <EMPH TYPE="ITAL">Klebsiella</EMPH> and <EMPH TYPE="ITAL">Escherichia coli</EMPH> in Nursing Homes

Abstract: Nursing home patients may be an important reservoir of ESBL-containing multiple antibiotic-resistant E coli and K pneumoniae. Widespread dissemination of a predominant antibiotic resistance plasmid has occurred. Use of broad-spectrum oral antibiotics and probably poor infection control practices may facilitate spread of this plasmid-mediated resistance. Nursing homes should monitor and control antibiotic use and regularly survey antibiotic resistance patterns among pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
280
4
14

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(309 citation statements)
references
References 37 publications
11
280
4
14
Order By: Relevance
“…72,73 As mentioned earlier, fluoroquinolone is one of the most common agents linked to this collateral damage, that is, the emergence of various kinds of pathogens. [21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37][38]71 However, the patterns of emergence vary among studies; no single study has demonstrated the impact of fluoroquinolone use on all of the specific antibiotic-resistant patterns. Differences in the hospital environments, hospital infection control policies, local microbial epidemiology, patient population and treatments, technology, or even study designs may influence the conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 As mentioned earlier, fluoroquinolone is one of the most common agents linked to this collateral damage, that is, the emergence of various kinds of pathogens. [21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37][38]71 However, the patterns of emergence vary among studies; no single study has demonstrated the impact of fluoroquinolone use on all of the specific antibiotic-resistant patterns. Differences in the hospital environments, hospital infection control policies, local microbial epidemiology, patient population and treatments, technology, or even study designs may influence the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,19 Despite the advantage of antibiotic prophylaxis, 13 a major concern remains on the potential of antibiotic prophylaxis to increase antibacterial resistance, particularly the influence of fluoroquinolone exposure. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] For example, emergence of fluoroquinoloneresistant bacteria in neutropenic patients receiving fluoroquinolone prophylaxis has been well-documented. [21][22][23][24][25][26][27][28][29] Furthermore, the occurrence of cross-resistant or multiple-drug-resistant (MDR) pathogens, such as an increase in MDR Gram-negative bacteria (GNB), 30,[35][36][37][38] increase in nosocomial methicillin-resistant Staphylococcus aureus infections 31,33,34,38,39 and an emergence of extended spectrum beta-lactamase producers, 32 have all been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The greater prevalence of resistance to common antibiotics has also been reported by other workers. 15,16 The presence of multidrug resistance may be related to the dissemination of antibiotic resistance among hospital isolates of E. coli. Among aminoglycosides, netillin was found to have an edge over gentamicin and amikacin.…”
Section: Discussionmentioning
confidence: 99%
“…Fazem parte da fl ora humana normal, assim como da de diversos animais, e são patógenos oportunistas de importância dentro e fora de hospitais, responsáveis por inúmeras doenças (Rodrigues 1997, Wiener et al 1999. Septicemias nosocomiais provocadas por esses microrganismos ocorrem frequentemente em pacientes entubados e submetidos a aspiração (Branger et al 1998).…”
Section: Discussionunclassified